Ketepatan Sasaran dalam Program Subsidi Pangan: Evaluasi Kualitatif atas Proses Targeting dan Verifikasi Data Rumah Tangga : Penelitian - Essi Laura Amanda (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to assess targeting accuracy in the Food Subsidy Program by analyzing the household data determination and verification process using a qualitative descriptive approach. Targeting accuracy is a crucial issue due to high levels of inclusion and exclusion errors, where non-poor households often receive assistance, while truly poor households are overlooked. The study found that the main problems stem from the quality of outdated social data, a lack of collaboration between agencies, and weaknesses in the inflexible management of the social registry. Furthermore, targeting methods such as the proxy means test (PMT) and community-based targeting also experience technical and social issues that affect the objectivity of the verification process. Field implementation is influenced by officer policies, limited resources, community pressure, and community dynamics, which often create bias in assessing household poverty status. The study findings suggest that improving data collection systems, strengthening social registry integration, increasing transparency in verification, and developing the capacity of field officers are essential steps to reduce targeting errors. Thus, this study provides comprehensive insight into the factors influencing the accuracy of food subsidy recipient determination and provides a basis for future policy improvements.